Diseño de un sistema de conducción y dos sistemas de riego para café en el Centro de Investigación del Café de Costa Rica - Saborío-Gutiérrez, Laura (Instituto Tecnológico de Costa Rica, 2018)
Due to climate change, the implementation of irrigation systems for coffee is becoming more common, although listening to it was very strange and unusual. Given this situation, two irrigation systems are carried out, in addition to driving, using the formulas and criteria learned during the Agricultural Engineering career. The majority of the data for the design was provided by CICAFÉ. For the drip irrigation system, self-compensating drippers are used to irrigate a sheet of 24.41 mm, in an irrigation time of 16.62 hours, for a system flow of 10.85 m3 / s, with a pressure in the valve of 11.34 mca. On the other hand, a sprinkler irrigation system was designed, which uses a 51.53 mm sheet, in a time of 9,79 hours, for a system flow of 4,20 m3 / h, with a pressure of the valve of 32.00 mca. A pump was chosen according to the requirements, in addition to a conduction system with a diameter of 3, which houses 12 water intakes that would be available for future projects. And finally the social, economic and environmental analysis was carried out.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018
Keywords: Café; Riego por goteo; Riego por aspersión; Diseño; Agua